2018
DOI: 10.1002/ams2.327
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future of Emergency General Surgery in the USA

Abstract: Emergency General Surgery (EGS) patients represent a unique group of acutely ill surgical patients at high risk for death and complications. Since the inception of EGS as a surgical subspecialty in the early 2000s, there have been significant developments to further define the scope of EGS as well as to advance data collection, performance measurement, and quality improvement. This includes defining the EGS cohort by diagnosis and procedure and by overall burden, benchmarking of EGS outcomes, and creation of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The provision of high quality and safe EGS care is a complex matter impacted by multifarious elements [27]. Not least among these is lack of access to the type of thorough and pragmatic datasets outlined above by Lyu et al [26]. This point has been previously supported by the American College of Surgeons (2013) in stating the case for a redesign of surgical care through the use of clinical registries.…”
Section: Egs Registrymentioning
confidence: 97%
See 1 more Smart Citation
“…The provision of high quality and safe EGS care is a complex matter impacted by multifarious elements [27]. Not least among these is lack of access to the type of thorough and pragmatic datasets outlined above by Lyu et al [26]. This point has been previously supported by the American College of Surgeons (2013) in stating the case for a redesign of surgical care through the use of clinical registries.…”
Section: Egs Registrymentioning
confidence: 97%
“…In a recent examination of the past, present, and future of Emergency General Surgery in the USA, Lyu et al [26] outline the significance of prospectively collected clinical data in order to suitably risk-adjust for the disparate EGS patient population. It is contended that the initiation of a robust EGS registry will facilitate both researchers and surgeons to engage in large, risk-adjusted studies to generate EGS-specific benchmarks and risk stratification systems.…”
Section: Egs Registrymentioning
confidence: 99%
“…Although emergency general surgery (EGS) and trauma patients have always been an integral part of surgical care, the field of acute care surgery (ACS) as a surgical specialty is a relatively new concept. ACS was initially proposed in 2005 as an innovative model of care to facilitate timely and high-quality EGS care along with trauma and surgical critical care 1 . Prior studies have demonstrated the ACS model can improve work flow and provide more effective delivery of care for patients with common urgent general surgery diagnoses without an increased rate of complications 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although emergency general surgery (EGS) and trauma patients have always been an integral part of surgical care, the eld of acute care surgery (ACS) as a surgical specialty is a relatively new concept. ACS was initially proposed in 2005 as an innovative model of care to facilitate timely and high-quality EGS care along with trauma and surgical critical care [1] . Prior studies have demonstrated the ACS model can improve work ow and provide more effective delivery of care for patients with common urgent general surgery diagnoses without an increased rate of complications [2] .…”
Section: Introductionmentioning
confidence: 99%